Influence of Oceanographic Parameters on The Results of The Catch of Squid (Loligo sp.) in The Java Sea (WPP-RI 712) - Fahrezy, Muhammad Alief Rizky; Perangin-angin, Robet; Istrianto, Kadi; Soepardi, Soegiono (PELAGICUS, 2024)
Information on oceanographic conditions is an important aspect to pay attention to because it is closely related to the existence of abundant squid resources. Most types of squid make seasonal migrations in response to changes in temperature. Squids will look for a place to attach their eggs under certain oceanographic conditions, such as the right salinity and water depth. Data collection was carried out primarily in the field using a 5 in 1 salinometer and secondarily using the AQUA MODIS satellite. Sea surface temperatures observed from the end of March to the beginning of May experienced a slow increase in temperature from day to day. Regarding water salinity, the data obtained is that the further out to sea, the greater the salinity tends to be. In chlorophyll a, there was a significant increase in March with the highest distribution. The influence of the measured oceanographic parameters on the number of squid catches, after chlorophyll-a cross-correlation was carried out, was 36.5% or a fairly strong correlation and the other 63.5% was estimated to influence other factors in the form of light, bulla, water depth, and current strength, as well as the crew's skills in operating fishing gear.